Reflecting on three years of CGIAR gender research - CGIAR Collaborative Platform for Gender Research (CGIAR Collaborative Platform on Gender Research, 2019)
From January 2017 through December 2019, the CGIAR Collaborative Platform for Gender Research (the ‘Gender Platform’) built on the system-wide gender network established in 2011 to increase the visibility and impact of CGIAR gender research; to develop capacity for doing better gender research in agriculture and natural resource management domains; to set and support a CGIAR-wide gender research agenda; and to foster strategic partnerships both internally and with key actors in the global gender research community. The Gender Platform was based in the CGIAR Research Program (CRP) on Policies, Institutions, and Markets (PIM) serving all CGIAR Research Programs and Centers and was coordinated by KIT Royal Tropical Institute. Modest resourcing came through core funding from the Gender Flagship of PIM, with individual CRPs and Centers supporting their researchers’ involvement. Additional bilateral support was mobilized through the European Commission, International Development Research Center (IDRC), Integrated Seed Sector Development (ISSD)-Africa and through joint projects with the CGIAR Platform for Big Data in Agriculture.